2019
DOI: 10.1016/j.cub.2019.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory and Neuromodulatory Signals Reverse Visual Object Avoidance to Approach in Drosophila

Abstract: Highlights d A fly's innate aversion to a small visual object is reversed by odor d Object valence is reversed by attractive odors but not an aversive one d Activating octopaminergic neurons is sufficient to reverse object valence d Motion-detecting neurons are necessary and sufficient to reverse object valence

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 80 publications
0
22
0
Order By: Relevance
“…Additional studies have shown that aminergic neurotransmitters can modulate visual information processing in flies and other insects [26,[41][42][43][44][45][46]. Octopamine, the invertebrate equivalent of noradrenaline, is present in processes innervating the medulla, lobula and lobula plate in Drosophila, where it regulates state-dependent modulation of visual interneurons [42,46] including the saliency of objects during flight [43]. Serotonergic neurons also innervate the optic ganglia [47][48][49][50][51][52] and previous studies indicate that serotonin impacts cellular activity and visual behaviors in insects [44,45,[53][54][55][56].…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies have shown that aminergic neurotransmitters can modulate visual information processing in flies and other insects [26,[41][42][43][44][45][46]. Octopamine, the invertebrate equivalent of noradrenaline, is present in processes innervating the medulla, lobula and lobula plate in Drosophila, where it regulates state-dependent modulation of visual interneurons [42,46] including the saliency of objects during flight [43]. Serotonergic neurons also innervate the optic ganglia [47][48][49][50][51][52] and previous studies indicate that serotonin impacts cellular activity and visual behaviors in insects [44,45,[53][54][55][56].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to elongated vertical bars, which flies steer toward, flies steer away from smaller objects, which are presumably interpreted as a threat (Maimon et al, 2008 ). This avoidance of small objects switches to attraction in the presence of an attractive odor, such as vinegar (Cheng et al, 2019 ). The presence of a food odor may signify that the small object is not a threat but in fact a potential food source.…”
Section: Modulation By Environmental Contextmentioning
confidence: 99%
“…The presence of a food odor may signify that the small object is not a threat but in fact a potential food source. This odor-dependent switch from visual aversion to attraction can be mimicked by optogenetically activating modulatory octopaminergic neurons or motion-sensitive visual pathways in the optic lobe (Cheng et al, 2019 ). Previous work showed that vinegar activates octopaminergic neurons innervating the visual system (Wasserman et al, 2015 ).…”
Section: Modulation By Environmental Contextmentioning
confidence: 99%
“…This modulation is consistent with, yet more subtle than, their free flight behaviour. It is worth noting that the difference between free flight [3] and tethered behaviour is also less pronounced in Drosophila [36]. Although the behavioural modulation we observed was subtle, quantifying the modulation allowed us to design a tethered preparation in which we could use calcium imaging to observe the neural basis for the behavioural modulation.…”
mentioning
confidence: 94%